Prasa i film II Rzeczypospolitej Polskiej wobec handlu białymi niewolnicami - Suchenek, Renata (Studia Europaea Gnesnensia, 2015)
This article presents, from a historical perspective, the role that the press and film played in the fight against slave trade in 2nd Republic of Poland, in the years 1918-1939. Source material for the paper had been obtained from state archives (the Archive of New Acts in Warsaw, the State Archive in Poznań) and the Archdiocesan Archive in Poznań, as well as excerpted from magazines and films from the period. Articles and press statements which provided information on human trafficking, human traffickers, socio-political countermeasures employed in Europe and in Poland conveyed the image of Polish involvement in the fight against human trafficking, the victims of which were Polish women. Films (scientific, feature films) were the means of propaganda in the fight against human trafficking, the main goal of which was mostly raising public awareness słowa klucze